2002
DOI: 10.1253/circj.66.943
|View full text |Cite
|
Sign up to set email alerts
|

Nicorandil Infusion Leads to Good Recovery From Ischemia of Left Ventricular Regional Work in Comparison With Nitroglycerin.

Abstract: icorandil (NR), a nicotinamide-nitrate ester [N-(2-hydroxyethyl)-nicotinamide nitrate)], is an antianginal drug with 2 characteristic functions: the conventional nitrate effect mediated by cyclic guanosine monophosphate (cGMP), and an independent ATP-dependent potassium channel-opening effect. [1][2][3][4][5] Nitrates induce arterial and venous dilatation of the epicardial coronary vessels, including the stenotic segment, by increasing cGMP within the vascular smooth muscle cells. 6-9 The potassium-channel ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…A clinical study [20] found that infusion of 0.5 Ag/kg/min nicorandil enhanced regional ventricular wall motion recovery during coronary angioplasty. Other studies of the effects of a similar dose of nicorandil on coronary angioplasty found maximal precon- ditioning effects of nicorandil during coronary angioplasty without collateral flow changes, as judged by ST-segment elevation and coronary artery pressure measurements in electrocardiograms [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study [20] found that infusion of 0.5 Ag/kg/min nicorandil enhanced regional ventricular wall motion recovery during coronary angioplasty. Other studies of the effects of a similar dose of nicorandil on coronary angioplasty found maximal precon- ditioning effects of nicorandil during coronary angioplasty without collateral flow changes, as judged by ST-segment elevation and coronary artery pressure measurements in electrocardiograms [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the NC dose in this study was conventional, based on several Japanese studies that used 0.50-0.55 μg/kg/minute of NC. 19,20) Suwa, et al demonstrated that the efficacy of carperitide in reducing mortality and subjective symptoms was not dosedependent. 7) However, the effects of carperitide on hemodynamics were not investigated in their study.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In many of these patients, the regional work of the nonischemic area gradually increased during balloon inflation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, sequential changes in LV regional function during PTCA have been reported in patients with normal LV function. [1][2][3] However, no prior studies have assessed these changes during PTCA in patients having a reduced LV function. Regional LV function was previously evaluated by calculating regional work using the relationship between mean wall stress and strain (the natural logarithm of the reciprocal of wall thickness).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation